THE EFFECT OF LEAFLET AND VIDEO METHODS OF HEALTH COUNSELING ABOUT INNECTICIDED GAMBUS IN MABODO PRIMARY HEALTH CARE: HEALTH COUNSELING - Zanuma Zanuma; Timbul Supodo; Sanihu Munir; Anry Hariadhin Depu (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:Puskesmas Mabodo is one of the Puskesmas with the most malaria cases out of 28 Puskesmas in Muna Regency in the last 2 years, with the 2018 API of 11.61 per 1,000 population and API in 2019 of 9,387 / 1,000 population. This study aims to determine the effect of extension methods on changes in the behavior of pregnant women in the use of insecticide-treated mosquito nets in the working area of ??Mabodo Health Center, Muna Regency. Methods:The type of research used is quantitative research, namely quasi-experimental research with a nonequivalent control group design. Result: The statistical test results obtained p value = 0.000 <0.05 between groups, this indicates that there are differences in respondent knowledge in each group, there are differences in respondent attitudes in all groups with p value = 0.033 <0.05 between groups, there are differences in respondent attitudes all groups p value = 0.011 <0.05 between groups. Conclusion: There is an effect of leaflet and video counseling on the use of textured bed nets in the working area of ??the Mabodo Health Center.